Anti-platelet activity of phytocompounds in various dandelion organs in human whole blood model in vitro. (May 2021) - Lis, Bernadetta; Rywaniak, Joanna; Jedrejek, Dariusz; Szustka, Aleksandra; Stochmal, Anna; Olas, Beata
Graphical abstract: Highlights: The anti-platelet potential of four fractions from various parts of dandelion in whole blood was studied. Fraction C reduced: the thrombus formation and platelets' activation upon stimulation with collagen. None of the tested fractions caused changes in the platelet proteome. Abstract: Numerous studies indicate that the usage of natural compounds, such as those found in dandelion, might modulate blood platelets' function. Our previous investigations indicated that fractions obtained from different organs of dandelion possessed anti-platelet properties and inhibited activation of washed platelets. However, the impact of those fractions on platelets in whole blood is still unknown. Therefore, the aim of the presented study was to evaluate the anti-platelet potential of four fractions obtained from various parts of dandelion (fractions A and B - roots; fraction C - leaves; fraction D - petals) on platelets activation and thrombus formation in whole blood and an impact of tested fractions on platelets' proteome. The level of activation of resting or agonist-stimulated (ADP or collagen) whole blood platelets after incubation with different dandelion fractions was determined based on their cell-surface expression of P-selectin (CD62P) and presence of an active form of GPIIb/IIIa (PAC-1 binding) by flow cytometry technique. The influence of the tested fractions on whole blood thrombus formation was estimated by the thrombus-formation analysis system (T-TAS). The changes in platelets' proteome after incubation with dandelion fractions were analyzed using gel electrophoresis (both, native and SDS-PAGE). We found that fraction C from dandelion leaves reduced: 1) the thrombus formation and 2) platelets' activation upon stimulation with collagen (statistically significant decrease in P-selectin expression and presence of an active form of GPIIb/IIIa) in whole blood. None of the tested fractions caused changes in the platelet proteome. This may represent a novel avenue of research on antiplatelet supplementation in the prevention and treatment of cardiovascular diseases caused by hyperactivation of platelets.